Criminological Review of Efforts to Counter Terrorism Crimes by Involving Civil Society: Research Study in Riau Islands Province - Andry Yosep Manalu; Dahlan Dahlan; Darwis Anatami; Soerya Respationo; Erniyanti Erniyanti (International Journal of Sociology and Law, 2024)
This research is motivated by the increasing threat of global terrorism and the importance of the role of civil society in the prevention and countermeasures of terrorism crimes. In Riau Islands Province, civil society involvement in security still faces various obstacles, including a lack of awareness, fear of reprisals, and a lack of resources, all of which have an impact on the effectiveness of counterterrorism efforts. The purpose of this study is to analyze the participation of civil society in counterterrorism efforts in the Riau Islands, identify the obstacles faced, and provide suggestions for increasing community involvement. The research method used is qualitative with a case study approach. Data is collected through in-depth interviews, observations, and analysis of documents related to security policies. Respondents included security forces, NGO activists, and civil society members involved in security initiatives. The results show that despite the recognition of the importance of community involvement, there are still shortcomings in the implementation of effective programs. These shortcomings include a lack of training, a lack of protection for whistleblowers, and a lack of resources. These barriers limit the active participation of the community in terrorism prevention and countermeasures activities. Based on the results of the study, it is recommended that the government increase the allocation of resources for community participation programs, develop safe and anonymous reporting mechanisms, and conduct extensive education and socialization programs to increase public awareness and skills in identifying and reporting suspicious activities. Security forces must also strengthen relations with civil society through more open communication and confidence-building